Development of FluoAHRL: A Novel Synthetic Fluorescent Compound That Activates AHR and Potentiates Anti-Inflammatory T Regulatory Cells - Jonić, N (2024)
Aryl Hydrocarbon Receptor (AHR) ligands, upon binding, induce distinct gene expression profiles orchestrated by the AHR, leading to a spectrum of pro- or anti-inflammatory effects. In this study, we designed, synthesized and evaluated three indole-containing potential AHR ligands (FluoAHRL: AGT-4, AGT-5 and AGT-6). All synthesized compounds were shown to emit fluorescence in the near-infrared. Their AHR agonist activity was first predicted using in silico docking studies, and then confirmed using AHR luciferase reporter cell lines. FluoAHRLs were tested in vitro using mouse peritoneal macrophages and T lymphocytes to assess their immunomodulatory properties. We then focused on AGT-5, as it illustrated the predominant anti-inflammatory effects. Notably, AGT-5 demonstrated the ability to foster anti-inflammatory regulatory T cells (Treg) while suppressing pro-inflammatory T helper (Th)17 cells in vitro. AGT-5 actively induced Treg differentiation from naïve CD4+ cells, and promoted Treg proliferation, cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) expression and interleukin-10 (IL-10) production. The increase in IL-10 correlated with an upregulation of Signal Transducer and Activator of Transcription 3 (STAT3) expression. Importantly, the Treg-inducing effect of AGT-5 was also observed in human tonsil cells in vitro. AGT-5 showed no toxicity when applied to zebrafish embryos and was therefore considered safe for animal studies. Following oral administration to C57BL/6 mice, AGT-5 significantly upregulated Treg while downregulating pro-inflammatory Th1 cells in the mesenteric lymph nodes. Due to its fluorescent properties, AGT-5 could be visualized both in vitro (during uptake by macrophages) and ex vivo (within the lamina propria of the small intestine). These findings make AGT-5 a promising candidate for further exploration in the treatment of inflammatory and autoimmune diseases.